The Interrelation of Balaghah and Egypt: Study of Amin al-Khuli's Thought - Syihabuddin, Muhammad; Manggala, Kayan; Nurkholisoh, Siti; Ansharah, Indana Ilma (Jurusan Pendidikan Bahasa Arab IAIN Ponorogo, 2024)
The essence of the science of Balaghah has been ingrained in the Arabic language to achieve creativity in both poetry and other literary forms. Al-Khuli in his book